Microleakage in Sub-Gingival Class II Preparations Restored Using Two Different Liners for Open Sandwich Technique Supplemented With or Without Ultrasonic Agitation: An In Vitro Study - Hitesh Chandar Gyanani; Naveen Chhabra; Nimisha Chinmay Shah; Pratik Subash Jais (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Probability of bond failure at sub-gingival cavosurface margin is high in class II cavity designs especially when margins are located in cementum or dentin. Previous researches have proved ultrasonics to be a beneficial tool in improving the marginal adaptation of the restorative material. Therefore, the effect of ultrasonic activation of the lining material at the gingival cavosurface margin was tested in the present research. Aim: The study aimed to evaluate the cervical micro-leakage in class II preparations with gingival margin located below cemento enamel junction and restored using open sandwich technique using two different liners and supplemented with or without ultrasonic agitation. Materials and Methods: Forty recently extracted human molars were collected, disinfected and stored in 0.9% saline solution. Standar dized class II cavities were prepared with gingival margin located 1mm below the cemento-enamel junction. Teeth were randomly divided into four groups (n=10) and restored using open sandwich technique as follows - Group A: Resin Modified Glass Ionomer Cement as liner and Beautifil II as coronal restoration; Group B: Same as group A supplemented with ultrasonic agitation; Group C: Beautifil Flow Plus as liner and Beautifil II as coronal restoration; Group D: Same as Group C supplemented with ultrasonic agitation. Prepared samples were subjected to thermo cycling, followed by immersing in 0.5% methylene blue dye solution. After 24 hours they were cleaned and sectioned in mesio-distal direction using diamond disc and evaluated for microleakage. Obtained scores were statistically analysed using one way ANOVA test and Post Hoc test. Results: Group B showed least microleakage amongst all groups but the results were statistically insignificant (p value > 0.05). Conclusion: Marginal adaptation of liner with ultrasonic activation was somewhat better however, the results were statistically insignificant.